2020
DOI: 10.1111/aos.14666
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection plays a role in conjunctival squamous cell carcinoma: a systematic review and meta‐analysis of observational studies

Abstract: Purpose We aimed to study the prevalence of human papillomavirus (HPV) in conjunctival intraepithelial neoplasia and carcinoma. Furthermore, we aimed to explore whether geographical differences or different detection modalities are associated with the conflicting information regarding HPV and the development of the disease. Methods We searched the MEDLINE, EMBASE and Scopus databases for studies reporting on HPV and conjunctival intraepithelial neoplasia or carcinoma. The pooled prevalence proportions, odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 54 publications
2
27
0
Order By: Relevance
“…Increasing evidence also supports the role of HPV in conjunctival CIN and SCC, and HPV status may also serve as an important biomarker in these diseases. With an odds ratio (OR) 8.42 (95%CI 3.70–19.16 in 21 studies) [ 35 ] and a risk ratio (RR) 3.13 (95%CI 1.72–5.71, 16 studies) [ 36 ] in two separate meta-analyses based on observational studies, HPV has shown to be strongly associated with an increased risk of conjunctival CIN and SCC. The prevalence estimates of HPV are 26% (95%CI 13–42%) in conjunctival CIN and 18% (95%CI 7–32%) in invasive SCC compared to 1% (95%CI 0–3%) among controls [ 35 ].…”
Section: The Conjunctivamentioning
confidence: 99%
See 4 more Smart Citations
“…Increasing evidence also supports the role of HPV in conjunctival CIN and SCC, and HPV status may also serve as an important biomarker in these diseases. With an odds ratio (OR) 8.42 (95%CI 3.70–19.16 in 21 studies) [ 35 ] and a risk ratio (RR) 3.13 (95%CI 1.72–5.71, 16 studies) [ 36 ] in two separate meta-analyses based on observational studies, HPV has shown to be strongly associated with an increased risk of conjunctival CIN and SCC. The prevalence estimates of HPV are 26% (95%CI 13–42%) in conjunctival CIN and 18% (95%CI 7–32%) in invasive SCC compared to 1% (95%CI 0–3%) among controls [ 35 ].…”
Section: The Conjunctivamentioning
confidence: 99%
“…With an odds ratio (OR) 8.42 (95%CI 3.70–19.16 in 21 studies) [ 35 ] and a risk ratio (RR) 3.13 (95%CI 1.72–5.71, 16 studies) [ 36 ] in two separate meta-analyses based on observational studies, HPV has shown to be strongly associated with an increased risk of conjunctival CIN and SCC. The prevalence estimates of HPV are 26% (95%CI 13–42%) in conjunctival CIN and 18% (95%CI 7–32%) in invasive SCC compared to 1% (95%CI 0–3%) among controls [ 35 ]. An overview of studies examining HPV in conjunctival intraepithelial neoplasia and carcinoma (39 studies) is provided in a recently systematic review by our group [ 35 ].…”
Section: The Conjunctivamentioning
confidence: 99%
See 3 more Smart Citations